2020
DOI: 10.3390/ma13112635
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Release of Growth Factors from Four Different Porcine-Derived Collagen Matrices

Abstract: Xenogeneic acellular collagen matrices represent a safe alternative to autologous soft tissue transplants in periodontology and implant dentistry. Here, we aimed to investigate the adsorption and release of growth factors from four porcine-derived collagen matrices using enzyme-linked immunosorbent assay. Non-crosslinked collagen matrix (NCM), crosslinked collagen matrix (CCM), dried acellular dermal matrix (DADM), and hydrated acellular dermal matrix (HADM) adsorbed each of the following growth factors, TGF-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 87 publications
2
24
0
Order By: Relevance
“…A study has been performed with biofunctionalization of mADMG along with autologous platelet concentrates like platelet-rich fibrin (PRF) and it was observed that there was an increased growth factor (vascular endothelial growth factor or VEGF), transforming growth factor-β [(TGF-β)] release and improved angiogenic potential after 7 days when compared to only PRF [ 46 ]. A similar functionalization pilot study on ADMGs with growth factors [fibroblast growth factor or FGF-2), TGF-β1, platelet-derived growth factor (PDGF-BB), and bone morphogenetic protein (BMP-2)] showed significant promise with improved adsorption and release of the growth factors [ 47 ]. Future clinical trials on the application of ADMGs along with platelet concentrates or growth factors in periodontal plastic surgical procedures are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A study has been performed with biofunctionalization of mADMG along with autologous platelet concentrates like platelet-rich fibrin (PRF) and it was observed that there was an increased growth factor (vascular endothelial growth factor or VEGF), transforming growth factor-β [(TGF-β)] release and improved angiogenic potential after 7 days when compared to only PRF [ 46 ]. A similar functionalization pilot study on ADMGs with growth factors [fibroblast growth factor or FGF-2), TGF-β1, platelet-derived growth factor (PDGF-BB), and bone morphogenetic protein (BMP-2)] showed significant promise with improved adsorption and release of the growth factors [ 47 ]. Future clinical trials on the application of ADMGs along with platelet concentrates or growth factors in periodontal plastic surgical procedures are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Parity between PCL3%-E and Mucograft ® , a commercially available collagen membrane used in oral soft tissue regeneration, was shown for the absorption and release of commercially available PL (a standardised and consistent product). A recent evaluation of Mucograft has shown a gradual, but high early release of protein within the first six hours [ 44 ]. Importantly for future clinical translation, the release of PL from PCL3%-E into the surrounding media also supports cellular attachment and proliferation of nearby MSCs [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the inherited ability of collagen to bind a number of proteins [ 7 ], we recently showed that the transforming growth factor-β1 (TGF-β1), fibroblast growth factor-2 (FGF-2), platelet-derived growth factor-BB (PDGF-BB), growth and differentiation factor-5 (GDF-5), or the bone morphogenetic protein-2 (BMP-2) can be adsorbed to commercially available porcine-derived collagen matrices with an efficiency close to 100%, and are then continuously released over time [ 8 ]. Furthermore, the four investigated collagen scaffolds have provided a favorable environment able to successfully promote the migration, adhesion, and proliferation of two oral cell types, namely primary human oral fibroblasts (hOF) and periodontal ligament cells (hPDLC) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%